Study of Living Wall Systems' (LWSs) Support system for improving LWSs Life cycle performance and noise reduction potential. (15th May 2022) - Chang, Lan-Ting; Chang, Feng-Cheng
Abstract: As urban crowding has increased globally, the construction industry has not commensurately focused on environmental sustainability or the quality of urban life. In this study, the use of ecofriendly living wall systems (LWSs) and their interactions with acoustic support systems (SSs) were investigated to develop a cost-effective urban greening strategy, emphasizing noise attenuation that promotes environmental sustainability and human health. Jacobaea maritima and recycled-plastic were used to create wood-plastic composites (WPC) for LWS-SSs, and their sound absorption coefficients ( α s ) were measured in a reverberation room. The results were compared with those of previous studies, indicating the following factors as influences on sound absorption: LWS weight and morphology, SS structure, additional panel absorbers, perforated board design, surface pattern, plant density, plant variety, substrate depth, and greenery coverage. SSs with simple acoustic designs compensated for deficiencies in LWS noise reduction capacity for frequencies under 1, 000 Hz. Compared with plants employed in previous studies, J. maritima achieved superior sound absorption and occupied less space. The interactions among factors suggest that weight, which determines the sound absorption capacity of the panels, is the key factor affecting the LWSs. The results also indicated that full greenery coverage is potentially unnecessary, given that slightly less greenery coverage was more cost-effective while still achieving considerable α s and aesthetic charm. To conclude, SS should be carefully considered when designing LWS, and WPC with molding flexibility can help LWS be adapted to diverse topographies. All the aforementioned factors can be adjusted to optimize the effectiveness of urban LWSs. Highlights: Support system (SS) designed for living wall system (LWS) boosts acoustic absorption. Recycled wood-plastic-composite SSs provide various ecofriendly potential with LWS. Jacobaea Maritima favorable in improving LWS noise reduction. To meet desired in situ acoustic effects, full greenery coverage is not necessary. LWS built effective absorbing sound at frequencies most influential to human.